Effect of soy milk consumption on glycemic status, blood pressure, fibrinogen and malondialdehyde in patients with non-alcoholic fatty liver disease: a randomized controlled trial. (June 2019) - Maleki, Zahra; Jazayeri, Shima; Eslami, Omid; Shidfar, Farzad; Hosseini, Agha Fatemeh; Agah, Shahram; Norouzi, Hamed
Highlights: We examined the effect of soy milk on some metabolic parameters in NAFLD patients. Soy milk caused a significant reduction in serum insulin and HOMA-IR. Soy milk had favorable effects on systolic and diastolic blood pressure. Abstract: Objective: Diet plays a critical role in the management of non-alcoholic fatty liver disease (NAFLD). Studies on the NAFLD's experimental models have reported that soy had positive effects on the improvement of metabolic parameters. However, there is a lack of clinical trials regarding the efficacy of whole soy foods. Therefore, this study was conducted to determine the effect of soy milk on some of the metabolic characteristics in patients with NAFLD. Methods: Sixty-sex patients diagnosed with NAFLD were included in this randomized, parallel, controlled trial and were randomly assigned to either the soy milk or control group. Both groups received a 500-deficit calorie diet plan. Also, patients in the soy milk group consumed 240 ml/day soy milk for 8 weeks. Fasting blood sugar (FBS), serum insulin, HOMA-IR, HOMA-β%, and QUICKI as well as serum malondialdehyde (MDA), plasma fibrinogen, and blood pressure (BP) were measured at the beginning and end of the study. Results: After 8-weeks of intervention, soy milk group had a greater significant reduction in serum insulin(-3.44 ± 5.02 vs. -1.09 ± 3.77 μIU/ml, P = 0.04), HOMA-IR (-0.45±0.64 vs -0.14 ± 0.47, P = 0.03), systolic (-3.81±4.15 vs -1.48±2.93 mmHg, P = 0.01) and diastolic (-2.39±2.80 vs. -0.94±2.76 mmHg, P = 0.04) BP, and also, a significant increase in QUICKI (0.02± 0.032 vs. 0.008±0.018, P = 0.04) compared to the control group. While, changes in the FBS, HOMA-β%, fibrinogen, and MDA were not significantly different between the study groups. Conclusion: A low-calorie diet containing soy milk had beneficial effects on serum insulin, HOMA-IR, QUICKI, and BP in patients with NAFLD.